Evaluasi Kinerja Pengawasan Service Road terhadap Pergerakan BTT/Baggage Towing Tracktor di Bandara Internasional Kualanamu Deli Serdang - Hanif Pradana; Ichyu Machmiyana; Dini Wagini (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to improve the performance of roadside supervision services for Baggage Towing Tractor (BTT) movements at Kualanamu International Airport, Deli Serdang. The research background is based on the high level of operational risk on the airside, which requires strict supervision of Ground Support Equipment (GSE) vehicles. The method used is descriptive qualitative with data collection techniques in the form of direct observation, semi-structured interviews, and field documentation. The results of the study indicate that violations of Standard Operating Procedures (SOP) such as excessive speeding, inappropriate lane use, and compliance with procedures are still common. The main causes include lack of training, weak monitoring systems, and low awareness of safety culture. From the results of the observation, it was found that supervision is still manual and not optimally supported by monitoring technology such as CCTV with a real-time integration system. In addition, the number of supervisory personnel is also not able to cover the entire service area of the road which is quite extensive, especially during peak operating hours. The lack of a firm reward and punishment system also contributes to the low discipline of BTT drivers. Interviews with several BTT operators showed that they have not received regular safety training, and most do not understand the importance of complying with established signs or markings. Therefore, it is recommended that airport authorities implement a monitoring system through the use of sensor-based technology and GPS tracking, as well as increase the intensity of occupational safety training. Furthermore, a dedicated unit should be established to continuously monitor GSE movements and integrate a digital reporting system to ensure prompt action on violations. Improving safety culture can also be achieved through internal campaigns and ongoing outreach.